Consensus and divergence in the social representations of political leadership - Torres Stöckl, Cynthia María (2015)
The aim of this paper is to analyze descriptively the consensual and differential dimensions of political leadership social representations, based on a convenience sample composed of Psychology, Philosophy and Humanities college students from Tucumán National University, Argentina. Results show a representational universe in tension characterized by opposite nuclear components: Leadership and Representation versus Power and Corruption, as well as opposite dimensions: Features / Positive Political Aspects versus Features / Negative Political Aspects, as well as two relevant clusters consistent with the latter two. Differences are also observed when analyzing variables such as: year in college, student’s political group membership, university political involvement and background / types of political figures.